Online Learning Evaluation during Covid-19 using CSE-UCLA Evaluation Model at English Education Department Universitas Kristen Indonesia - Lamhot Naibaho (Budapest International Research and Critics University, 2021)
This research is about the online learning evaluation during covid-19 using the CSE-UCLA evaluation model. It is was aimed to evaluate the implementation of online learning during COVID-19. This research was done at Universitas Kristen Indonesia (UKI) using a qualitative approach with an evaluative study design is the CSE-UCLA evaluation model design. The subjects of this study were lecturers and students and were taken through purposive sampling. The instruments used in this research were questionnaires and interviews, observations, and documentation. The data analysis technique used in evaluating online learning use at the UKI is based on the assessment system components, program planning, program implementation, program improvement, and including good criteria, in terms of quality level improvement programs including good program certification. The study's result was that, in general, the quality level of the online learning used at the UKI is already in good criteria. When viewed from the component system assessment level of quality including good criteria, in terms of quality level planning program including good criteria, in terms of quality level implementation of the program criteria, and when viewed from quality level certification programs also include good criteria.